A fast chemical exchange saturation transfer imaging scheme based on single‐shot spatiotemporal encoding. Issue 5 (27th April 2016) - Huang, Jianpan; Zhang, Miao; Lu, Jianhua; Cai, Congbo; Chen, Lin; Cai, Shuhui
Abstract : Purpose: To design a new approach that can not only keep the spatial and temporal resolution but also have better built‐in immunity to magnetic field inhomogeneity and chemical shift effects than the single‐shot echo planar imaging (EPI) for chemical exchange saturation transfer (CEST) MRI. Method: The single‐shot spatiotemporally encoded (SPEN) MRI sequence was combined with a continuous wave saturation pulse for fast CEST MRI (CEST‐SPEN MRI). The resulting images were super‐resolved reconstructed by a hybrid method that solves the l 1 norm minimization together with total variation (TV) regularization. Partial Lorentzian fitting was used to analyze the subsequent Z‐spectra. Results: Experimental results of a creatine phantom and in vivo tumor rat brains show that CEST‐SPEN MRI has good capability in providing CEST‐based and NOE‐based contrast images. Conclusions: Compared with CEST‐EPI, CEST‐SPEN MRI has better immunity to magnetic field inhomogeneity and provides better contrast images within identical acquisition time, especially under an identical inhomogeneous field. Magn Reson Med 77:1786–1796, 2017. © 2016 International Society for Magnetic Resonance in Medicine